Experiencing digital fashion archives through a decolonial lens - Victoria Rodriguez Schon; Julia Valle-Noronha (European Journal of Cultural Management and Policy)
Fashion archives, as repositories of cultural memory, often reflect and perpetuate colonial legacies through their curation, classification, and accessibility practices. This paper investigates how digital technologies can serve as transformative tools for decolonising fashion archives, enabling inclusive knowledge production and equitable access. Grounded in a postphenomenological framework, the study explores user interactions with digitalised archives. Using a case study approach, this research examines exemplary initiatives where cultural institutions have leveraged digital tools to reimagine archival narratives. The selected cases highlight the potential of digital innovation to preserve intangible heritage and foster dynamic experiences. Findings reveal how digital technologies mediate the relationship between cultural artefacts and audiences, challenging traditional power structures within heritage institutions. By drawing connections between decolonial archival praxis and empirical outcomes, this paper provides actionable insights for researchers, archivists, curators, and designers aiming to build archives through a decolonial lens. This study contributes to the broader discourse on heritage, decolonisation, and digital transformation within the fashion sector, offering a roadmap for bridging the physical and digital realms.